Agribusiness incubation in niger growing tribal FPOs in Andhra Pradesh: Agribusiness incubation in niger growing tribal FPOs in Andhra Pradesh - V RAJENDRA PRASAD; M SRINIVASA RAO; M SURESH KUMART; P SEETHA RAMU; P JOGA RAO; B N SANDEEP (Journal of Oilseeds Research, 2023)
The area under Niger witnessed a reduction from around 8000 ha in 2012-13 to 3729 ha in 2021-22 in Andhra Pradesh. Sustaining and enhancing the area, production and productivity of Niger will enhance the house hold food security and income security of small and marginal tribal households. Hence a study has been undertaken in High Altitude and Tribal Zone (HAT) of Andhra Pradesh with the objective to explore the possibilities of FPO’s in orienting thier activities towards Niger cultivation, value addtion, branding and marketing of the Niger oil.